2015
DOI: 10.1016/j.jpeds.2015.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in the Critically Ill Child: Frequency and Related Factors

Abstract: Constipation is common in critically ill children. Body weight, Pediatric Index of Mortality 2 clinical severity score, admission after surgery, and the need for vasoconstrictor therapy are major independent risk factors associated with constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 25 publications
1
32
1
1
Order By: Relevance
“…However, gastric aspiration might be useful for detecting tube dislocation when gastric retention does not solely consist of gastric secretion . The prevalence of constipation was 7%, which is much lower than previously reported in a study of critically ill children (prevalence of 46.7%) . Of note, we did find a large number of infants (62%) who vomited at least once when on PE‐formula.…”
Section: Discussioncontrasting
confidence: 66%
“…However, gastric aspiration might be useful for detecting tube dislocation when gastric retention does not solely consist of gastric secretion . The prevalence of constipation was 7%, which is much lower than previously reported in a study of critically ill children (prevalence of 46.7%) . Of note, we did find a large number of infants (62%) who vomited at least once when on PE‐formula.…”
Section: Discussioncontrasting
confidence: 66%
“…Surprisingly, constipation, which is frequent in critically ill children, is less commonly considered as a sign of feeding intolerance in PICU. A study of 150 children [17] found constipation occurred in 47% of children who spent more than 3 days in the PICU. A number of factors influenced the development of constipation (defined as 3 days without a bowel movement) including immobility, opiates and other commonly used PICU drugs, delayed enteral feed administration, splanchnic hypoperfusion, inflammation, sepsis, and electrolyte disturbances (most notably hypercalcemia, hypokalemia, hypomagnesemia, and hypophosphatemia).…”
Section: Bowel Sounds and The Frequency Of Bowel Movementsmentioning
confidence: 99%
“…A number of factors influenced the development of constipation (defined as 3 days without a bowel movement) including immobility, opiates and other commonly used PICU drugs, delayed enteral feed administration, splanchnic hypoperfusion, inflammation, sepsis, and electrolyte disturbances (most notably hypercalcemia, hypokalemia, hypomagnesemia, and hypophosphatemia). They found a significantly higher incidence in surgical patients and in older higher weight children, in addition to those who received little enteral nutrition which was started later [17]. Diarrhea (still inadequately defined in neonates and small infants) can also occur in critically ill children, although the reported incidence is lower than that reported in critically ill adults of 15-38% [36,47].…”
Section: Bowel Sounds and The Frequency Of Bowel Movementsmentioning
confidence: 99%
“…In this sample, 15.2% of patients before and 13.6% of patients after the implementation remained on the ICU. As shown by Lopez and colleagues () in their study on one ICU, the prevalence of constipation was very high. It was for this reason that we suggest a similar education program for the ICU nurses in order to decrease the constipation rate.…”
Section: Discussionmentioning
confidence: 70%